Vitamin D-VDR signaling in bone cells - Braziunas, Denise (2014)
Vitamin D plays a key role in mineral homeostasis, in which its main biological effect is to maintain adequate serum calcium levels. The systemic deficiency of either 1,25D or its receptor (VDR) is associated with bone alterations such as rickets and osteomalacia. This review summarizes the evidence supporting a direct effect of vit D-VDR on bone cells. The presence of vit D-hydroxylases as well as VDR in several cell types, supports an autocrine I paracrine role for vitamin D. Bone-derived cells also express VDR, and thus it is currently hypothesized that 1,25(OH)2 vitamin D (1,25D) directly controls specific aspects of bone and mineral homeostasis. Several forms of vitamin D have been shown to induce specific and direct effects on different cells from bone and cartilage, such as chondrocytes, osteoblasts, osteocytes, osteoclasts and bone marrow stromal cells. Both catabolic and anabolic effects of vitamin D have been demonstrated in bone, mediated by different signal transduction mechanisms. In addition to the classic VDR mediated actions, non-classic and rapid effects of vitamin D have also been demonstrated in bone cells.